Social, Economic and Competitiveness aspects of Green Innovation - Borsatto , Jaluza Maria Lima Silva; Pimenta, Daiana Paula; Bazani, Camila Lima; Jesuka, Duterval (Advances in Scientific and Applied Accounting, 2024)
Objective: The purpose of this study is to analyze how the adoption of green innovation practices by companies can affect the economic (Gross Domestic Product - GDP), social (Human Development Index - HDI) and competitiveness (Global Competitiveness Index - GCI) Development of Developed Countries (DC) and Emerging Countries (EC). Method: For the analysis, a three-level hierarchical regression model was used with repeated measures and estimated by Maximum Likelihood from a sample of 4061 publicly traded companies, 80% of which from the G7 countries and 20% from the BRICS (Brazil, Russia, India, China, and South Africa). Results: The results showed that in relation to GDP, all green innovation indicators negatively influenced economic development in both DC and EC. With regard to the HDI, green innovation practices such as environmental management and environmental investments positively influence social development in DCs and ECs, respectively. As for competitiveness, the results revealed that only green innovation practices related to environmental policies showed statistically significant results demonstrating a negative relationship with the GCI both in the DC and in the EC. Contributions: The study contributes with possible ways for companies and governments to set goals to achieve Sustainable Development Goals, SDG-8 to promote sustainable and inclusive economic growth, SDG-9 to promote inclusive and sustainable industrialization and foster innovation, and SDG-10 to strengthen and revitalize the global partnership for sustainable development.